Comparative of Neutrophils and Lymphocyte Ratio for Dairy Cattle in Prepartum and Postpartum Condition - Diza Raudya Tuzzahra; Eko Fuji Ariyanto; Septiyani -; Aziiz Mardanarian Rosdianto (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2022)
There is a transition period that dairy cattle always pass through in their reproduction cycle, making them more stressed. Stress can simply be identified by the ratio of neutrophil (N) and lymphocyte (L) at the haematologic state of dairy cattle. The purpose of this study is to evaluate stress conditions in dairy cattle’s transition period based on neutrophil and lymphocyte ratio. Twenty samples of dairy cattle’s blood in prepartum and postpartum condition are being analyzed with a hematology analyzer. The result of this study shows that the average of neutrophil has increased insignificantly from prepartum to postpartum period as 4.14 103/µL ± 1.51 to 4.27 103/µL ± 2.08 or 1.03% with a normal interval of neutrophil is 1.7-6.0 103/µL. However, the average of lymphocytes decreased insignificantly from 3.23 103/µL ± 1.13 to 3.03 103/µL ± 1.23 or 0.93% with a normal interval of lymphocyte is 1.8-8.1 103/µL. Then, the average of neutrophil and lymphocyte ratio has increased insignificantly from 1.35 103/µL ± 0.46 to 1.47 103/µL ± 0.60 or 1.09%. Based on this result, the ratio of neutrophils per lymphocyte still in the normal range. In the transition period, only a few dairy cattle have a stressful condition. The stress condition in dairy cattle can be identified by increasing neutrophil (neutrophilia) and reducing lymphocyte (lymphocytopenia).